2018
DOI: 10.7717/peerj.5626
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive scale Gaussian filter to explain White’s illusion from the viewpoint of lightness assimilation for a large range of variation in spatial frequency of the grating and aspect ratio of the targets

Abstract: The variation between the actual and perceived lightness of a stimulus has strong dependency on its background, a phenomena commonly known as lightness induction in the literature of visual neuroscience and psychology. For instance, a gray patch may perceptually appear to be darker in a background while it looks brighter when the background is reversed. In the literature it is further reported that such variation can take place in two possible ways. In case of stimulus like the Simultaneous Brightness Contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Considering just the MW stimuli, despite the smaller area of the flanker modulator compared to the assimilator, the flanker modulator still generated a surprisingly strong lightness induction effect, which suggests that if one were to control for modulator area, then the flanker effect may have been even stronger. Relatedly, it has been reported that the lightness induction of the MW stimulus does not depend on the aspect ratio of the target region, and hence the overall aspect ratio of the stimulus (Blakeslee & McCourt, 2004;Blakeslee, Padmanabhan & McCourt, 2016;Güçlü & Farell, 2005), but conflicting reports do exist (Mitra et al, 2018). Although, the magnitude of the MW stimulus has been shown to be resilient across a wide range of lower spatial frequencies, and demonstrates an increase across higher spatial frequencies (Blakeslee & McCourt, 2004;Helson & Rohles, 1959;White, 1979).…”
Section: Lightness Illusion Differencesmentioning
confidence: 99%
“…Considering just the MW stimuli, despite the smaller area of the flanker modulator compared to the assimilator, the flanker modulator still generated a surprisingly strong lightness induction effect, which suggests that if one were to control for modulator area, then the flanker effect may have been even stronger. Relatedly, it has been reported that the lightness induction of the MW stimulus does not depend on the aspect ratio of the target region, and hence the overall aspect ratio of the stimulus (Blakeslee & McCourt, 2004;Blakeslee, Padmanabhan & McCourt, 2016;Güçlü & Farell, 2005), but conflicting reports do exist (Mitra et al, 2018). Although, the magnitude of the MW stimulus has been shown to be resilient across a wide range of lower spatial frequencies, and demonstrates an increase across higher spatial frequencies (Blakeslee & McCourt, 2004;Helson & Rohles, 1959;White, 1979).…”
Section: Lightness Illusion Differencesmentioning
confidence: 99%
“…Blakeslee and McCourt [10][11][12][13] attempted to interpret effects like White's and others, for example simultaneous brightness contrast and grating induction using multiscale spatial filtering). They also determined that the effect also appears in the early stage of cortical filtering operations in the human visual system.…”
Section: Introductionmentioning
confidence: 99%